SENAM HAMIL DALAM MENURUNKAN KELUHAN KRAM KAKI PADA IBU HAMIL TRIMESTER III - Dessy Hidayati Fajrin; Zabariah (Rena Cipta Mandiri, 2024)
Cramps in pregnant women can occur due to a lack of blood circulation to the lower part of the body, which is usually obstructed due to increased body weight and pressure in the uterus. One solution to avoid leg cramps is to do pregnancy exercises. Pregnancy exercises can optimize physical balance, attitude and movement during pregnancy, reduce physical complaints such as back pain and muscle spasms. The purpose of this research is to provide midwifery care to pregnant women by doing pregnant exercises in reducing leg cramps in third trimester pregnant women. This research was conducted using case study methodology, field observation, and descriptive qualitative methods. This study used one respondent. The results obtained were reduced leg cramps after routine pregnancy exercises. The conclusion that can be obtained is that pregnant gymnastics can reduce the intensity of leg cramps in third trimester pregnant women.